Safety and efficacy of BAY 94‐9027, a prolonged‐half‐life factor VIII. (22nd February 2017) - Reding, M. T.; Ng, H. J.; Poulsen, L. H.; Eyster, M. E.; Pabinger, I.; Shin, H.‐J.; Walsch, R.; Lederman, M.; Wang, M.; Hardtke, M.; Michaels, L. A.
Abstract : Essentials Recombinant factor VIII BAY 94‐9027 conjugates in a site‐specific manner with polyethylene glycol. BAY 94‐9027 was given to patients with severe hemophilia A as prophylaxis and to treat bleeds. BAY 94‐9027 prevented bleeds at dose intervals up to every 7 days and effectively treated bleeds. BAY 94‐9027 treatment was mainly well tolerated and no patient developed factor VIII inhibitors. Click to hear Dr Tiede's perspective on half‐life extended factor VIII for the treatment of hemophilia A Summary: Background: BAY 94‐9027 is a B‐domain‐deleted prolonged‐half‐life recombinant factor VIII (FVIII) that conjugates in a site‐specific manner with polyethylene glycol. Objective: Assess efficacy and safety of BAY 94‐9027 for prophylaxis and treatment of bleeds in patients with severe hemophilia A. Patients/methods: In this multinational, phase 2/3, partially randomized, open‐label trial, men aged 12–65 years with FVIII < 1% and ≥ 150 exposure days to FVIII received BAY 94‐9027 for 36 weeks on demand or prophylactically at intervals determined following a 10‐week run‐in period on 25 IU kg −1 body weight two times per week. Patients with > 1 bleed during the run‐in subsequently received 30–40 IU kg −1 two times per week; patients with ≤ 1 bleed were eligible for randomization to every‐5‐days (45–60 IU kg −1 ) or every‐7‐days (60 IU kg −1 ) prophylaxis (1 : 1) for 26 additional weeks until randomization arms were filled. Patients who were eligible but not randomized continued twice‐weekly prophylaxis. The primary efficacy outcome was annualized bleeding rate (ABR). Results: The intent‐to‐treat population included 132 patients (prophylaxis, n = 112; on demand, n = 20). Median ABR (quartile [Q1; Q3]) for patients treated two times per week who were not eligible for randomization ( n = 13) improved after dose increase (17.4 [14.3; 26.0] to 4.1 [2.0; 10.6]). Median ABR for patients randomized to every‐5‐days treatment ( n = 43) was 1.9 (0; 4.2), similar to patients eligible for randomization but who continued treatment two times per week ( n = 11). Median ABR for 32/43 patients (74%) who continued every‐7‐days prophylaxis until study end was 0.96 (0.0; 4.3). Six hundred and thirty‐six of 702 bleeds (90.6%) were controlled with ≤ 2 infusions. No patient developed a FVIII inhibitor. Conclusions: BAY 94‐9027 prevented bleeding across three individually tailored dose regimens and was effective for treatment of bleeds.